LANGUAGE AS A FACTOR OF ETHNIC IDENTITY AND ISSUES OF INTERETHNIC RELATIONS: COMMON AND SPECIAL IN THE HISTORY AND MODERNITY OF KYRGYZSTAN AND CHUVASHIA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines problems related to linguistic and ethnic identity and the role of languages in interethnic relations in a multiethnic society. Linguistic and ethnic identity are interrelated categories. A person often correlates his perception of belonging to a certain ethnic group with what language he speaks and uses, or what language he accepts as his native language. Features of ethnic identity are traced through the example of the historical fate and aspects of the modern socialsituation of two Turkic languages – Kyrgyz and Chuvash – and their speakers. Some common features and differences associated with the past and present of the Kyrgyz and Chuvash are noted. An attempt has been made to analyze the dynamics of the demography of these languages using census data, starting with the USSR census in 1989 and up to the 2020s. in the Russian Federation and the Kyrgyz Republic. As a result of the study, a conclusion is made about the importance for the languages of a few ethnic groups of such a factor as knowledge of a second language; in the case of the Chuvash and Kyrgyz, this is currently the same language – Russian, although the former live within the Russian Federation, and the latter are the titular ethnic group of a sovereign state – Kyrgyzstan.
Keywords: Chuvashia, Kyrgyzstan, ethnic identity, language, interethnic relations